Structural fire behaviour of aluminium alloy structures: Review and outlook. (1st October 2022) - Wang, Zhongxing; Li, Mengyu; Han, Qinghua; Yun, Xiang; Zhou, Kan; Gardner, Leroy; Mazzolani, Federico M.
Highlights: Research studies on mechanical characteristics of aluminium alloys in and after fire are reviewed. Structural fire behaviour of members, connections, joints and overall systems is discussed. Passive and active fire protection measures for aluminium alloy structures are presented. An outlook for the future research in this field is presented. Abstract: Aluminium alloys are gaining increasing use in the construction industry, underpinned by extensive research and the growing availability of codified structural design rules at room temperature. More recently, considering that the material properties of aluminium alloys degrade significantly at elevated temperatures, a substantial number of studies have also been conducted to investigate the behaviour and design of aluminium alloy structures exposed to fire. This paper presents a review of recent studies on the mechanical characteristics of aluminium alloys in fire and after fire, as well as the structural behaviour of aluminium alloy structures in fire conditions, considering members, connections, joints and overall systems. In addition, possible passive and active fire protection measures for aluminium alloy structures are introduced and discussed. Lastly, recommendations for future work on the structural fire behaviour of aluminium alloy structures are set out, providing insight into aspects that require further investigations to promote the more widespread use of aluminium alloys in structural applications.